2019
DOI: 10.1002/art.40841
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety During Treatment With Baricitinib in Rheumatoid Arthritis

Abstract: Objective To assess the frequency of cardiovascular and venous thromboembolic events in clinical studies of baricitinib, an oral, selective JAK1 and JAK2 inhibitor approved in more than 50 countries for the treatment of moderately‐to‐severely active rheumatoid arthritis (RA). Methods Data were pooled from 9 RA studies. Placebo comparison up to 24 weeks included data from 6 studies. Randomized dose comparison between baricitinib doses of 2 mg and 4 mg used data from 4 studies and from the associated long‐term e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 49 publications
4
112
1
7
Order By: Relevance
“…Two GI perforations were reported in the upadacitinib arm; however, these were not spontaneous perforations, but rather 1 was a case of peritonitis and 1 was an anal abscess. In this trial, VTEs were reported in all treatment arms, consistent with the reported background risk for VTE in RA irrespective of the treatment (41)(42)(43)(44)(45). The proportion of patients with VTEs was balanced in the first 6 months of this trial across all treatment arms, including placebo and adalimumab.…”
Section: Discussionsupporting
confidence: 75%
“…Two GI perforations were reported in the upadacitinib arm; however, these were not spontaneous perforations, but rather 1 was a case of peritonitis and 1 was an anal abscess. In this trial, VTEs were reported in all treatment arms, consistent with the reported background risk for VTE in RA irrespective of the treatment (41)(42)(43)(44)(45). The proportion of patients with VTEs was balanced in the first 6 months of this trial across all treatment arms, including placebo and adalimumab.…”
Section: Discussionsupporting
confidence: 75%
“…Patients in the A3921133 randomized, endpoint-driven postauthorization safety study had a diagnosis of RA, were aged ≥ 50 years, and had one or more cardiovascular risk factor. Based on the safety analysis of study A3921133 and knowledge of the safety profile of other Janus kinase inhibitors [49,50], venous thromboembolism events (including deep vein thrombosis and PE) were identified as an important risk for treatment with tofacitinib, irrespective of dose. Subsequently, thromboembolism was added as a warning and as an adverse drug reaction to the current product labeling for tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
“…DVT/PE events have been reported in rheumatoid arthritis clinical studies of other Janus kinase inhibitors including baricitinib (all baricitinib doses: DVT IR: 0.4; PE IR: 0.2) and upadacitinib (all upadacitinib doses: DVT: 0/329 patients through Week 12; 1/498 patients through Week 24; PE: 2/329 patients through Week 12; 6/498 patients through Week 24) . All patients with DVT/PE events in the rheumatoid arthritis studies of the Janus kinase inhibitors baricitinib and upadacitinib had additional DVT/PE risk factors …”
Section: Introductionmentioning
confidence: 99%
“…doses. 5 7,8 Reported literature values for IRs of thromboembolic events among persons with rheumatoid arthritis treated with a variety of biologic and/or conventional therapies ranged between 0.04-0.79. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Rheumatoid arthritis is a known risk factor for DVT/PE events, with a risk ratio for DVT of 2.08 and a risk ratio for PE of 2.17 for rheumatoid arthritis vs nonrheumatoid arthritis, based on a metaanalysis of nine observational studies in patients with rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%